2019
DOI: 10.4254/wjh.v11.i6.553
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ribavirin treatment failure in Asian organ transplant recipients with chronic hepatitis E infection

Abstract: BACKGROUND Hepatitis E virus (HEV) infection is a cause of chronic hepatitis in immunosuppressed patients. Sustained virologic response rates to a 12-wk course of ribavirin therapy were reported to be > 70% in the West. This study describes the outcome of HEV treatment in a transplant center in Singapore. AIM To study the outcome of ribavirin treatment in a series of chronic HEV patients, and the cause of treatment failure. METHODS We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In addition, 27 studies 5,14,15,18,22,26–47 were evaluated for the second arm on HEV treatment, including 118 LT recipients (6 of them with dual liver/kidney and 1 with liver/heart recipients) treated with various regimens for HEV infection (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 27 studies 5,14,15,18,22,26–47 were evaluated for the second arm on HEV treatment, including 118 LT recipients (6 of them with dual liver/kidney and 1 with liver/heart recipients) treated with various regimens for HEV infection (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty seven studies 5,14,15,18,22,26–47 (16 case reports, 2 case series, 9 cohorts) reported the outcomes of 118 LT recipients with confirmed HEV infection Table 3. Median age of patients was 55 (32–64) years old and mean time from transplantation was 19 (2–216) months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment effect of RBV was described in 34 studies 22,23,25‐27,32,34‐36,38‐62 . The majority of the 395 patients treated with RBV was male, and almost all patients were SOT recipients.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, clinical guidelines recommend a program therapy duration of 12 weeks using RBV at the initiation with a weight-adjusted dose or a dose adjusted on the basis of the estimated glomerular filtration rate [12,13,23]. Following these recommendations, a total of 176 transplant patients have been reported, and 129 of these patients have achieved SVR (73.2%) [11,[24][25][26][27][28][29][30][31][32][33]. Therefore, this recommendation seems to be highly effective for the treatment of HEV infection in transplant recipients infected by genotype 3 HEV.…”
Section: Discussionmentioning
confidence: 99%